2020
DOI: 10.5590/ijmat.2020.19.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Ways to Reduce Restaurant Industry Food Waste Costs

Abstract: Food waste costs U.S. restaurant leaders billions of dollars per year. The purpose of this research was to provide restaurant leaders with processes and strategies to reduce food waste costs. The research method used was systematic literature review in addressing this research question: What processes and strategies are available to U.S. restaurant leaders to reduce food waste costs? This study addresses a gap in literature related to processes and strategies to reduce food waste costs. Six processes and seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Bartłomiej emphasizes in his paper [12] the need for organizational improvements leading to the decrease of food waste and costs in restaurants. While the literature does report applications of lean management in service businesses, the literature contains few works on specific applications in the domain of food services [13][14][15]. Lean management was found to be useful in three study cases from Poland to decrease food waste and reduce operational costs.…”
Section: Waste Management In the Restaurant Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Bartłomiej emphasizes in his paper [12] the need for organizational improvements leading to the decrease of food waste and costs in restaurants. While the literature does report applications of lean management in service businesses, the literature contains few works on specific applications in the domain of food services [13][14][15]. Lean management was found to be useful in three study cases from Poland to decrease food waste and reduce operational costs.…”
Section: Waste Management In the Restaurant Industrymentioning
confidence: 99%
“…Summarizing the research in this area, the most significant impediments to improving sustainability in the restaurant industry are: lack of adequate knowledge and information on the side of both restaurant owners/managers and customers, the nature of the restaurant industry, regular customers and tourists that can impact the increase of food wastes in restaurants, lack of appropriate knowledge and technology in dealing with eco-waste management, design of the menus, and complexity in operations of a restaurant [3,6,11,15,33].…”
Section: Waste Management In the Restaurant Industrymentioning
confidence: 99%
“…However, in another study conducted, it showed that the most common practice for food that has not been consumed or food surplus is by simply throwing them away (Filimonau & Coteau, 2018). Restaurant leaders and managers in this context, should identify where opportunities for food surplus management practices exist and the appropriate strategies and targets to set to mitigate restaurant food waste (Blum, 2020).…”
Section: Introductionmentioning
confidence: 99%